Agricultural contamination impacts antibiotic resistance gene abundances in river bed sediment temporally. Issue 9 (13th July 2018) - Beattie, Rachelle E; Walsh, Michael; Cruz, Mercedes Cecilia; McAliley, L Rex; Dodgen, Laurel; Zheng, Wei; Hristova, Krassimira R
ABSTRACT: Kewaunee County, Wisconsin is an agricultural area dominated by concentrated animal feeding operations and manure fertilized cropland. The objective of this study was to characterize chemical and antibiotic resistance gene (ARG) profiles of 20 surface water locations in Kewaunee County to better understand relationships between agricultural contamination and ARG abundance over one year. Surface water (n = 101) and bed sediment (n = 93) were collected from 20 sites during five timepoints between July 2016 and May 2017. Samples were analyzed for six genes ( erm (B), tet (W), sul1, qnrA, intI1 and 16S rRNA) and water chemistry and pollution indicators. qnrA, intI1 and sul1 genes in surface water were significantly higher than erm (B) and tet (W); however, no difference was present in sediment samples. Redundancy analysis identified positive correlations of nitrate, Escherichia coli, and coliforms with tet (W) and intI1 genes in sediment and intI1, sul1 and tet (W) genes in water. Temporal patterns of ARG abundance were identified with significantly higher gene abundances found in sediment during Kewaunee County's manure fertilization period; however, surface water patterns were not distinct. Together, these results suggest Kewaunee County sediments serve as a site of accumulation for non-point source agricultural pollution and ARGs on a temporal scale associated with manure fertilization. Abstract : Agricultural contamination increases antibiotic resistance genes in sediments in Kewaunee County, Wisconsin, on a temporal scale associated with the manure fertilization period.